PENGARUH SOSIAL MEDIA INFLUENCER TERHADAP PEMBELIAN KOSMETIK HALAL - Muhamad Gamal Abdullah; Ayu Ekasari (STMIK Widuri Jakarta, 2025)
This study aims to analyze the influence of social media influencers on the purchase of cosmetic products in Indonesia, by considering variables such as attitude toward the SMI, perceived credibility, perceived expertise, subjective norm, perceived behavioral control, and purchase intention. The research applies a quantitative approach by distributing questionnaires to 270 social media users who have purchased halal cosmetic products. The analysis method used is Structural Equation Modeling (SEM) with the help of AMOS 22 software. The results show that perceived credibility, perceived behavioral control, and subjective norm significantly affect the attitude toward the influencer, which in turn influences purchase intention. Religiosity acts as a moderator that strengthens the relationship between attitude toward the SMI and purchase intention. These findings highlight the importance of choosing the right influencer in the marketing strategy of halal cosmetic products in Indonesia.